2001
DOI: 10.1055/s-2001-15120
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of L-Triiodothyronine in Acetylcholine Metabolism in Adult Rat Cerebrocortical Synaptosomes

Abstract: Despite the recently emerging notion of thyroid-hormone involvement in neurotransmission in the adult mammalian brain, adequate evidence for a cellular basis of the process is still lacking. The present study indicates the involvement of thyroid hormones in cholinergic system of the adult rat cerebral cortex. Administration of L-triiodothyronine (T3, 0.025 to 4 microg/g) in single doses increased the synaptosomal acetylcholinesterase (AchE) and Mg2+-ATPase activity maximally at 24 hours in a dose-dependent way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…3). The high local synaptosomal level of T3 might have caused a depression in the AChE activity, exerting a feedback inhibition or toxic-inhibitory effect (Sarkar and Ray, 2001). Moreover, there are evidences to correlate the inhibition of synaptosomal Na + -K + -ATPase activity with the release of ACh and enhanced activity of AChE and vice versa (Meyer and Cooper, 1981).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…3). The high local synaptosomal level of T3 might have caused a depression in the AChE activity, exerting a feedback inhibition or toxic-inhibitory effect (Sarkar and Ray, 2001). Moreover, there are evidences to correlate the inhibition of synaptosomal Na + -K + -ATPase activity with the release of ACh and enhanced activity of AChE and vice versa (Meyer and Cooper, 1981).…”
Section: Discussionmentioning
confidence: 97%
“…Synaptosomal acetylcholinesterase (AChE, EC 3.1.1.7) activity was estimated according to the method of Ellman et al (1961), with slight modifications (Sarkar and Ray, 2001). Briefly, the synaptosomal suspension was incubated in a medium containing 60 mM Tris-HCl buffer (pH 7.4) and 5 mM acetyl-thiocholine iodide for 30 min at 37°C.…”
Section: Assay Of Acetylcholinesterasementioning
confidence: 99%
“…Cell culture studies have shown that the amount of cell membrane-bound esterase activity is inversely proportional to Tc-99m ECD uptake (Walovitch et al, 1994). Thyroid axis hormonal changes have been demonstrated in animal studies to modulate esterase production and activity in both a positive and a negative manner, depending in part on the particular type of esterase and the biochemical milieu (Goswami and Rosenberg, 1985;Banerjee and Ray, 2002;Takahashi et al, 2001;Sarkar and Ray, 2001). Given the aberrations in acid-base balance and electrolyte metabolism known to occur during hypothyroidism (Moses and Scheinman, 1996), the probable resultant pH changes, and the pH-related ionization and trapping of ligands with the same N 2 S 2 structure as ECD (Verbruggen, 1998), it is plausible that a pH change in the biochemical brain milieu, with secondary effects on esterase production and function, may contribute to local changes in Tc-99m ECD retention during hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the critical role of thyroid hormones (THs) in brain development and metabolism, recent investigations have highlighted the involvement of these hormones in the adult mammalian brain neurotransmission [1][2][3][4]. In particular, a very close association exists between the THs and brain cholinergic function [5].…”
Section: Introductionmentioning
confidence: 99%